Pemberdayaan Ekonomi Masyarakat Desa melalui Unit Pengumpulan Zakat: Analisis Kelembagaan di Mojopuro, Wonogiri - Nada Sofa Mariyah; Syauqi Syahla Ibtisamah; Fauzun Jamal (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the role of the Zakat Collection Unit (UPZ) of Mojopuro Village, Wonogiri, in empowering the rural economy through an institutional perspective. Using a qualitative case study approach, the research explores the formation of UPZ, its organizational structure, and its strategy in managing zakat for community empowerment. The findings indicate that the institutional strengthening of UPZ provides an essential foundation for transparent and accountable zakat management at the village level. The orientation toward productive zakat reflects a shift from consumptive distribution to capacity building for mustahik through locally based economic activities. However, the sustainability of UPZ programs is influenced by several challenges, including limited managerial capacity, operational funding constraints, and strong traditions of direct zakat distribution. Despite these limitations, coordination with BAZNAS and community participation enhance the potential for institutional sustainability. This study concludes that village-based UPZ can function as an effective instrument for rural economic empowerment when supported by strong institutional governance, continuous capacity development, and public trust